(untitled) (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2018)
The use of technology in support of corporate or organizational activities is currently growing, one of which is in the operational data processing company or organization. Technology that is currently widely used for data processing is a computerized system, with a computerized data processing system, can be done quickly and accurately. Women Empowerment Cooperative Prima Resources Jakarta is a cooperative savings and loan, currently processing transaction data is still done manually, both for savings transactions, loans, and reporting, so that allows errors in the recording, paper easily lost and torn because it is still in the form of archives, the limitations in search of necessary data, and less accurate reports made. with the design of computerized saving and loan system is expected to be a solution in solving the existing problems in this cooperative, in this design the author uses the user center design (UCD) as a method to analyze how the design of savings and loan information systems viewed from the user or user, so that system designed in accordance with the needs of users, the results of this study is the application of savings and loan information system accompanied by a database that has been tailored to the needs of users, then tested against the system that has been created using the method black box